2002
DOI: 10.1016/s1470-0328(02)01962-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study of misoprostol and gemeprost in combination with mifepristone for induction of abortion in the second trimester of pregnancy

Abstract: Objective To compare the effectiveness of gemeprost and misoprostol as prostaglandins used in combination with mifepristone for induction of mid-trimester termination. Design Randomised trial.Setting Scottish teaching hospital.Sample One hundred women undergoing abortion between 12 and 20 weeks.Methods Each woman received 200 mg mifepristone and 36-48 hours later either 1 mg gemeprost vaginal pessary every 6 hours for 18 hours or 4 Â 200 Ag misoprostol tablets vaginally followed by 2 Â 200 Ag misoprostol table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…Based on a previous study [10], to achieve an 80% power to detect a difference of less than 6% in the efficacy of the two methods and to allow completion of the recruitment in time, a minimum of 100 patients were needed (50 in each group).…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previous study [10], to achieve an 80% power to detect a difference of less than 6% in the efficacy of the two methods and to allow completion of the recruitment in time, a minimum of 100 patients were needed (50 in each group).…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] The manufacturer's recommendation is to use 600 mg of mifepristone, but randomised controlled trials have shown that 200 mg of mifepristone is as effective as 600 mg. [10][11][12] The use of prostaglandins has been well studied in relation to dose, type and route of administration. [13][14][15][16][17][18][19] Misoprostol is cheap, does not require special storage conditions and is as effective as gemeprost 14,20 and prostaglandin E 2 21 in mid-trimester abortion. Gemeprost is no longer obtainable in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats combinés de six études randomisées [25][26][27][28][29][30] regroupant plus de 450 femmes permettent de montrer qu'il n'y a pas de différence significative entre les taux d'expulsion à 24 heures, ainsi qu'entre le délai moyen entre le début de l'induction et l'expulsion. En revanche, il existe une différence significative en termes de dose d'analgésique utilisée et le taux d'expulsion incomplète.…”
Section: Les Prostaglandinesunclassified